Zero waste MSW management challenges in Klaipėda district - Tumaševičiūtė, Rasa; Zigmontienė, Aušra (International Conference “Environmental Engineering”, 2017)
Production volumes are increasing by growing economy and consumption processes. Industry and other eco nomic activities generate municipal solid waste stream. With growth of the industry, economy and pace of consumption major key is to avoid municipal solid waste (MSW) generation. The majority of developing countries are seeking to alter the prevailing waste management practices and to adapt the concept of Zero Waste society. This study aims to provide guidance in Klaipėda district and gives an opportunity to become the first district in Lithuania, which provides an objective assessment of the public municipal waste management service area and identifies the real situation of the municipal waste management sector. This paper develops that the path towards Zero Waste society is essential for the approximation of the different waste treatment technologies. To achieve this objective is a difficult task because the solution requires a holistic approach to waste generation, collection, processing and disposal. The main conclusions of the study offers a major challenges faced by Klaipėda district of limited data quantifying and characterizing waste generation patterns also suggesting that “way to Zero Waste” society require renewed governmental leadership as well as founding of effective national regulatory framework to reduce waste generation or conserve resources.